Associations between Ambulatory Blood Pressure Parameters and Cerebral White Matter Lesions - Cristina Sierra (International Journal of Hypertension)
Silent cerebral white matter lesions (WMLs) are a common finding on magnetic resonance imaging of the brain in the elderly. However, in patients with hypertension, WMLs tend to occur earlier in life and appear to be more severe. There is a body of evidence that supports the idea that WMLs in asymptomatic hypertensive patients should be considered a silent early marker of brain damage. It is known that ambulatory blood pressure monitoring (ABPM) correlates more closely with hypertension-related organ damage than office blood pressure. This paper focuses on the associations between blood pressure parameters obtained by 24-hour ABMP and cerebral WMLs.